Study of the influence of the structure of rolled iron on its hardness - Hlushkova, D.; Volchuk, V.; Panamariova, O.; Глушкова, Діана Борисівна; Волчук, Володимир Миколайович; Панамарьова, Ольга Борисівна (Харківський національний автомобільно-дорожній університет, 2023)
The structure of the material determines its properties, but it is impossible to establish a mutually unambiguous correspondence between the parameters of the structure and the properties using traditional methods. Topicality. As shown in many studies, the fractal (small) dimension of the structural elements of many materials correlates with their properties. The purpose of the work. Investigate the influence of the structure of cast irons on their hardness using multifractal analysis. Materials and methods. The spectrum of statistical dimensions of the cast iron microstructure was calculated using the Renyi formula. The hardness of chromium-nickel cast iron was determined at three points of the sample. Results of experiments. It was found that the pairwise correlation coefficients for predicting hardness by traditional structure characteristics (length, diameter, area) were R 2 = 0.73...0.87. When assessing hardness indicators by multifractal characteristics, the correlation coefficients are 0.78...0.88 for the pearlite structure with flake graphite and 0.81...0.93 for the pearlite structure with spherical graphite. The sensitivity coefficients of the hardness indicators of СПХН-43 rolls to the information and correlation dimensions of carbides, as well as to the fractal and statistical D-100 dimensions of flake graphite were determined. The sensitivity of hardness indicators to the fractal and statistical D100 dimensions of carbides and to the fractal and correlation dimensions of flake graphite was determined for СПХНФ-47 rolls. Conclusions. Based on the results obtained, an approach to assessing the hardness of СПХН-43 and СПХНФ-47 rolls was developed, which includes: 1). Determination of the statistical dimension spectrum of the cast iron structure elements. 2). Determination of the sensitivity coefficients of hardness indicators to the spectrum of dimensions of structural elements. 3). Creation of a mathematical model for predicting the hardness of rolls. The considered approach can be interpreted as an alternative method for assessing the quality criteria of cast irons based on the analysis of their structure.
Дослідження впливу структури валкового чавуну на його твердість
Keywords: structure; multifractal; sensitivity; model; forecast; quality criteria; структура; мультифрактал; чутливість; модель; прогноз; критерії якості; 620.175.2:669.15; 10.30977/BUL.2219-5548.2023.103.0.122